Pelatihan Pembuatan Minuman Jawor (Jahe Wortel) sebagai Peluang Usaha Masyarakat di Desa Ciberuem Kecamatan Cisarua Bogor - Sari Wardhani, Hilda; Ardi Noegraha, Rosandi; Sari Harsanti, Pradnya; Farrah, Farrah (Bulletin of Community Engagement, 2024)
The purpose of this research is to provide training on innovations in making drinks from carrots to the people of Cibeureum village, Cisarua - Bogor. The method used ABCD (Asset Based Community) to maximize the potential assets, which includes individual assets, communities, infrastructure, community, et al. The the activity of making Jawor Drink (Ginger Carrot) as a business opportunity for the community in Ciberuem Village, Cisarua District, Bogor, is a training method. Pertiwi University Tourism students as instructors provide ideas and also training to the community to turn agricultural products into business opportunities that can help economic development. The people of Cibeureum village are very enthusiastic about the new innovation developed by Pertiwi University students regarding drinks made from carrots. Jawor drink is believed to be a new drink innovation that can be enjoyed in Cibeureum village which has cool weather qualities. Keywords: Learning Herbal Drink, Community Service, Community Business Opportunities